A model-based analysis of physiological properties of the striatal medium spiny neuron. (2nd December 2015) - Wang, Jing; Liu, Shenquan; Wang, Hongchu; Ju, Niansheng; Zeng, Yanjun
Abstract : As the principal cell of the striatum, medium spiny neurons (MSNs) are closely associated with various motor dysfunctional diseases. In this paper, we describe an electric compartment model constructed in NEURON with a realistic morphology. Based on a 554-compartment computational model, we researched the influence of external current stimuli, different ions conductance, and the removal of partial dendrites on the physiological properties of the MSN. The main results are the following: (1) in the case of external current stimuli, various firing patterns appear in the MSN and the model produces a clear period-adding bifurcation phenomenon; (2) the effect of distinct types of ion channels vary and significant differences in discharge rhythm exist even among ion channels of the same type; (3) the closer the removed dendrite was to the soma, the larger the impact this had on the discharge pattern of the MSN.